1999
DOI: 10.1128/jcm.37.10.3328-3331.1999
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Helicobacter pylori Antibodies in a Pediatric Population: Comparison of Three Commercially Available Serological Tests and One In-House Enzyme Immunoassay

Abstract: A serum immunoglobulin G enzyme immunoassay (EIA) forHelicobacter pylori antibodies already in use in adults was evaluated with 99 pediatric serum samples to determine its usefulness for the study of H. pylori disease in children. The reference method used was either the 13C-urea breath test or a biopsy culture of gastric mucosa. In children, an EIA cutoff of 0.35 absorbancy unit yielded sensitivity, specificity, and positive and negative predictive values of 93, 97, 93, and 97%, respectively. The cutoff recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…pylori closely related species [22]. In our study, we not found false-positive result; hence, no absorption step was considered necessary.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…pylori closely related species [22]. In our study, we not found false-positive result; hence, no absorption step was considered necessary.…”
Section: Discussionsupporting
confidence: 39%
“…Whole cell lysate is the best choice of antigen as compared to a purified antigen which unable to recognize various type of antibodies present in the population. A different population may harbor different natures of H. pylori antigen [22]. H. pylori local strain antigen is useful with enough influence on the diagnostic properties of serological assay [18].…”
Section: Discussionmentioning
confidence: 99%
“…Third, the students were evaluated using only urine and serum tests to identify whether a subject is H. pylori infected. Some reports have suggested that the antibody test is inaccurate for the diagnosis of H. pylori infection in children, 29,30 but the both serum and urine antibody kits showed a good diagnostic accuracy. [17][18][19] On the other hand, a strength of the present study is that both urine and serum antibody tests were performed for H. pylori infection diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The performances of several kits have been evaluated in several articles [22][23][24][25]. Three meta-analyses performed on a general or pediatric population have been published [26][27][28].…”
Section: Discussionmentioning
confidence: 99%